Peran Lingkungan Sosial dalam Membentuk Karakter Siswa - Chairany, Revicia; Siregar, Nadia Aqila Karim; Dwianti, Chantika (EL-EMIR Institute, 2025)
This study aims to examine the role of the social environment in shaping students' character through a qualitative approach with a literature study method. Students' character is not only formed through formal education at school, but is also greatly influenced by the surrounding social environment, such as family, peers, society, and social media. In this study, the author analyzed various literatures and previous research results to identify social factors that play an important role in character formation. The results of the study indicate that the social environment has a significant influence on the development of moral values, attitudes, and behavior of students. Positive social interactions tend to shape good character, such as honesty, responsibility, and empathy. Conversely, a negative social environment can hinder the development of ideal character. These findings emphasize the importance of synergy between schools, families, and communities in creating a conducive environment for the formation of superior student character.